Experimental Study on Coal Permeability and Damage Evolution Under the Seepage-Stress Coupling - Lin, Fujin; Huang, Guangli; Jiang, Deyi; He, Yi; Fan, Jinyang (Frontiers in Earth Science, 2022)
In order to study the damage evolution law of coal under the seepage-stress coupling, this paper adopted the rock servo triaxial test system to conduct permeability test for full stress-strain process on 10 sets of coal specimens using steady-state method under different confining pressure and osmotic pressure. The results show that coal permeability has a small fluctuation before the stress peak, and the permeability increases substantially after the peak. The relationship between the plastic damage variable of coal and the equivalent plastic strain is proposed. The research will provide a theoretical basis for hydraulic fracturing gas drainage reservoir.